19th Annual Symposium on Foundations of Computer Science (Sfcs 1978) 1978
DOI: 10.1109/sfcs.1978.32
|View full text |Cite
|
Sign up to set email alerts
|

Selection and sorting with limited storage

Abstract: Abstnact. When selecting fnom, on sorting, a file stored on a reao-only tape and the irrternal storage is nather linritedrseveral !'asses o-f the inpr-rt tape may be requir,ed. h-e strrdy the relation befween t}'re arnount of internal stor"age availabl-e and the number of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
200
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(200 citation statements)
references
References 1 publication
0
200
0
Order By: Relevance
“…For discussion simplification, we assume that a data element has a single value and the total order means an increasing order of data values. Rank-Element (RE) Query: Given a rank r, find the element with rank r. It was shown [20] that any algorithm for computing exact φ-quantiles of an ordered set of N data elements requires Ω(N 1/κ ) space if κ scans of the data set are allowed. Consider that quantiles computation may be immediately transformed to RE queries.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…For discussion simplification, we assume that a data element has a single value and the total order means an increasing order of data values. Rank-Element (RE) Query: Given a rank r, find the element with rank r. It was shown [20] that any algorithm for computing exact φ-quantiles of an ordered set of N data elements requires Ω(N 1/κ ) space if κ scans of the data set are allowed. Consider that quantiles computation may be immediately transformed to RE queries.…”
Section: Problem Statementmentioning
confidence: 99%
“…Among various statistics, order statistics computation is one of the most challenging, and is employed in many real applications, such as web ranking aggregation and log mining [1,12], sensor data analysis [14], trends and fleeting opportunities detection in stock markets [3,23], and load balanced data partitioning for distributed computation [25,27]. Most order statistics computation problems require memory size linearly proportional to the size of a data stream for exact answers by one-scan techniques [1,20]; this may be impractical in data stream applications where streams are massive in size and fast in arrival speed. Consequently, approximate computation is a good alternative.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a one-pass algorithm to compute approximate quantiles has been given by Munro and Paterson [20]. Utilizing the knowledge on the data distribution, Alsabti, et al, have presented an algorithm to estimate the quantile values with provable error bounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the knowledge on the data distribution, Alsabti, et al, have presented an algorithm to estimate the quantile values with provable error bounds [21]. A distribution independent quantile estimation [22] can also be done in one pass with error guarantees that costs less memory than [20], [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The study of upper bounds on the time-space trade-off for sorting was initiated by Munro and Paterson [11] who gave a time-space focused algorithm in a model with tapeinput. For algorithms with random access input the first fully scalable, and till now the best upper bound for the time-space trade-off was given by Frederickson [8], who showed that for ÐÓ Ò Ë Ḉ Òµ there exists a comparison RAM algorithm sorting Ò keys in time Ì and space Ë such that Ì ¡ Ë Ḉ Ò ¾ ÐÓ Òµ.…”
Section: Related Workmentioning
confidence: 99%